Perhitungan Unit Cost Rawat Inap VIP Rumah Sakit Umum Daerah Kabupaten Klungkung Tahun - Estrada Adhi Saputra, I Ketut (Community Health)
RSUD Kabupaten Klungkung ,up to now, can not afford to cover its operational cost. This is because income gained from inpatient care especially from VIP ward was not optimal. This study aimed is to calculate unit cost from inpatient care VIP A,B,C and Maha Utama RSUD Kabupaten klungkung. This research is a case study using direct activities in inpatient care unit and indirect activities in supporting unit as a study object. Datas are collected through literature study from hospital reports and participation observation to find out activities happen during the production process. Research found that the higher direct cost is in Maha Utama ward, which was Rp 166.596 and the lowest is in VIP C ; Rp 138.697. On the other hand, the  highest indirect cost is in VIP C ; Rp 144.377 and the lowest is in Maha utama ; Rp 144.330. From the calculation, unit cost of inpatient care services  in VIP A, B, C and Maha utama are different one to another : Rp. 291.525, Rp. 284.112, Rp. 283.344 and Rp. 310.925 respectively. This study concluded that hat unit cost for inpatient care was increase along with the inpatient room level.